Response of chilli (Capsicum annuum L.) to organic and inorganic mulches (Indian Journal of Arid Horticulture, 2025)
A field study was conducted to evaluate the effect of different mulch materials on growth, yield and qualitative characters of chilli (cv. Bullet) from Feb to June 2013. Different mulches used were black polyethylene mulch, yellow polyethylene mulch, transparent polyethylene mulch, mango leaf, paddy straw, saw dust and sun grass and bare soil was the control. Different mulches generated higher soil temperature and moisture regimes over the control. Weed population was significantly suppressed under black polyethylene mulch. Days to 50 per cent flowering and days to first harvest were recorded at 44.93 and 46.23 days after transplanting under black polyethylene mulch as compared to rest of the treatments.. Plant height, number of primary branches per plant, number of leaves, fruit yield, average fruit weight recorded higher values under black polyethylene mulches however, it failed to have significant impact on fruit quality parameters.
Keywords: Chilli; mulching; yield; qualitative traits